All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 98423 by mathmax by abdo last updated on 13/Jun/20
calculate∫0∞e−x2−1x2dx
Answered by maths mind last updated on 14/Jun/20
=∫0∞e−(x−1x)2−2dx...t=1x⇒=∫0+∞e−(t−1t)2−2dtt2⇒2∫0+∞e−x2−1x2dx=e−2∫0+∞(1+1t2)e−(t−1t)2u=t−1t=e−2∫−∞+∞e−u2du=e−2.π⇒∫0+∞e−x2−1x2dx=π2e2
Commented by abdomathmax last updated on 14/Jun/20
thankssir.
Commented by maths mind last updated on 14/Jun/20
withepleasur
Terms of Service
Privacy Policy
Contact: info@tinkutara.com